2017
DOI: 10.3892/mmr.2017.8065
|View full text |Cite
|
Sign up to set email alerts
|

Icariin ameliorates dexamethasone‑induced bone deterioration in an experimental mouse model via activation of microRNA‑186 inhibition of cathepsin K

Abstract: The present study aimed to investigate bone deterioration in glucocorticoid-induced osteoporosis (GIOP) mice, and the anti-osteoporosis effect and underlying molecular mechanism of icariin. Dexamethasone (DSM) treatment was demonstrated to facilitate the induction of hypercalciuria in GIOP mice. Icariin treatment reversed the dexamethasone (DXM)-induced disequilibrium of calcium homeostasis and bone resorption, and increased serum alkaline phosphatase, tartrate resistant acid phosphatase, osteocalcin and deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…Liu et al found that icariin had beneficial effects for osteoporotic rats via the inhibition of peroxisome proliferator-activated receptor γ (PPARγ) and Notch2 mRNA expression (Liu et al, 2017a). And Ma et al found that icariin appears to be a therapeutic drug to manage glucocorticoid-induced bone loss via the activation of microRNA-186-mediated suppression on cathepsin K (Ma et al, 2018). Additionally, icariin could significantly reduce particle-induced bone resorption by suppressing osteoclast formation (Shao et al, 2015).…”
Section: Natural Chinese Medicinesmentioning
confidence: 99%
“…Liu et al found that icariin had beneficial effects for osteoporotic rats via the inhibition of peroxisome proliferator-activated receptor γ (PPARγ) and Notch2 mRNA expression (Liu et al, 2017a). And Ma et al found that icariin appears to be a therapeutic drug to manage glucocorticoid-induced bone loss via the activation of microRNA-186-mediated suppression on cathepsin K (Ma et al, 2018). Additionally, icariin could significantly reduce particle-induced bone resorption by suppressing osteoclast formation (Shao et al, 2015).…”
Section: Natural Chinese Medicinesmentioning
confidence: 99%
“…( 54 ) miR‐186 has been shown to inhibit cathepsin K and the PI3K‐AKT pathway in mice, affecting osteoarthritis and drug‐induced bone deterioration. ( 55,56 ) miR‐19a‐3p and miR‐186‐5p are expressed in bone, brain, and spinal cord tissue as well as in whole blood, ( 57 ) so it is reasonable that these miRNAs may be acting on bone or the SNS (Supplemental Fig. S4 A ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, both of miR-186 and miR-21 can negatively regulate gene expression by binding to the 3′-untranslated region (3′-UTR) of PTEN mRNAs, leading to mRNA degradation or translational repression (Bermúdez Brito et al, 2015;Feng et al, 2019). Interestingly, icariin can upregulate these miRNAs (Lian et al, 2018;Ma et al, 2018), suggesting a possibility of that miR-186 or miR-21 may mediate the inhibitory effects of icariin on PTEN. However, our RT-qPCR results revealed that neither Ab nor icariin affected the expression levels of miR-186 and miR-21 in SK-N-MC cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%